2015
DOI: 10.1080/14719037.2015.1028973
|View full text |Cite
|
Sign up to set email alerts
|

Agencification and Public Sector Performance: A systematic comparison in 20 countries

Abstract: The increased establishment of semi-autonomous agencies in most countries from the 1980s on has been justified by claims of expected improvement in public sector performance. Empirical research to test these claims has been scarce, based on single cases and showing mixed results. This study tests these claims at the macro level in twenty countries using a range of indicators and variables. Overall, we find a negative effect of agencification on both public sector output and efficiency. This refutes the economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 51 publications
3
76
3
2
Order By: Relevance
“…In some cases, such as in the tax case in this study, blame deflection can be observed, but this does not seem to work in the police case. Combined with the notion that agencification is associated with negative effects on public sector efficiency (Overman and Van Thiel 2016), the decision to set up a semiautonomous agency to deliver public tasks could be costly and might yield less than expected.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, such as in the tax case in this study, blame deflection can be observed, but this does not seem to work in the police case. Combined with the notion that agencification is associated with negative effects on public sector efficiency (Overman and Van Thiel 2016), the decision to set up a semiautonomous agency to deliver public tasks could be costly and might yield less than expected.…”
Section: Discussionmentioning
confidence: 99%
“…Bach, 2012;Pollitt et al, 2001). On the other hand, a recent study found a negative effect of agencification on both public sector output and efficiency (Overman and Van Thiel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Waluyo, 2013b), and conducted at the macro level (e.g. Overman and van Thiel, 2015). Agencification has scarcely been researched from the viewpoint of accounting and financial reporting (Waluyo, 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also indicates towards the sensitivity of the results of different studies and attributes it to the problems of data type, specification of the underlying models and econometric techniques. Overman and Van Thiel (2016) identified different aspects of public sector performance including efficiency, effectiveness, compliance, implementation, quality, meeting standards of good governance, sustainability, and so on. It is evident that productivity of public expenditure plays important role in both fiscal adjustment and its sustainability, particularly in situations when the government has limited resources at its disposal to support public services.…”
Section: Review Of Literature and Theoretical Frameworkmentioning
confidence: 99%